Osteoporosis and Bisphosphonate-Related Osteonecrosis in a Dental School Implant Patient Population. Issue 3 (June 2015) - Al-Sabbagh, Mohanad; Robinson, Fonda G.; Romanos, Georgios; Thomas, Mark V.
Abstract : Purpose: Studies have demonstrated an inconsistent association between implant failure and bone mineral density. The prevalence of osteoporosis in US adults has been reported to range from 5% to 10% in women and from 2% to 4% in men. The prevalence of bisphosphonate (BP)-related osteonecrosis of the jaw (BRONJ) has been reported to range from 0% to 4.3% of patients taking oral BPs. The purpose of this study was to calculate the risk of dental implant loss and the incidence of BRONJ in patients with osteoporosis at the University of Kentucky College of Dentistry (UKCD). Materials and Methods: This study analyzed data collected from patients who had implants placed between 2000 and 2004 at UKCD. Data were gathered from patient interviews regarding implant survival and patient-satisfaction parameters, and interviews were conducted either chairside at a scheduled maintenance appointment or by telephone interview. Results: Among 203 patients who received 515 implants, the prevalence of osteoporosis was 23.3% for women and 1.2% for men. None of the 20 patients who reported a history of oral BP use exhibited BRONJ, and there were no implant failures in patients with a history of osteoporosis. Conclusions: In this study, osteoporosis conferred no risk of implant failure, and oral BP therapy was not associated with BRONJ.